A multidimensional approach to understanding the value deficiencies that drive enterprise transformation. Issue 1 (2nd January 2016) - McCarthy, Nicola; Serban, Nicoleta; Rouse, William
ABSTRACT: It is crucial for an enterprise in a dynamic market to understand both realized and potential performance. This allows the enterprise to counteract anticipated value deficiencies before they are actually experienced. Our multidimensional model of superior performance identifies the dimensions of realized and potential . Experienced performance in relation to rivals, whether superior or inferior, is measured as the dimension of realized. Anticipated performance, whether superior or inferior (an anticipated value deficiency), is projected as the dimension of Potential. We validate our approach by applying a functional data analysis methodology to our data set of 397 firms. Our findings confirm that performance cannot be fully explained with reference to just one dimension, confirming the importance of accurately estimating potential performance in dynamic markets.